Differential Mechanisms of Plasminogen Activator Inhibitor-1 Gene Activation by Transforming Growth Factor-β and Tumor Necrosis Factor-α in Endothelial Cells - Chen, Yan Q.; Sloan-Lancaster, Joanne; Berg, David T.; Richardson, Mark A.; Grinnell, Brian; Tseng-Crank, Julie (Thrombosis and Haemostasis, 2001)
Plasminogen activator inhibitor-1 (PAI-1) is a serine protease inhibitor (SERPIN) specific for tissue-type and urokinase-like plasminogen activators. High plasma PAI-1 activity is a risk factor for thrombotic diseases. Due to the short half-life of PAI-1, regulation of PAI-1 gene expression and secretion of active PAI-1 into the blood stream is important for hemostatic balance. We have investigated transcriptional control of PAI-1 gene expression in bovine aortic endothelial cells (BAECs) and human cell lines using PAI-1 5’ promoter-luciferase reporter assays. Contrary to the cytokine-induced up-regulation of PAI-1 mRNA and protein levels, we found that only transforming growth factor-β (TGF-β) was efficient in inducing PAI-1 promoter activation. Tissue necrosis factor-α (TNF-α) induced a small luciferase activity with the 2.5 kb PAI-1 promoter, but not with the PAI-800/4G/5G and p3TP-lux promoters. Next we investigated whether a lack of response to TNF-α was due to deficient signaling pathways. BAECs responded to TNF-α with robust NFκB promoter activation. TGF-β activated the p38 MAP kinase, while TNF-α activated both the SAPK/JNK and p38 MAP kinases. The ERK1/2 MAP kinases were constitutively activated in BAECs. BAEC therefore responded to TNF-α stimulation with activation of the MAP kinases and the NFκB transcriptional factors. We further measured the messenger RNA stability under the influence by TGF-β and TNF-α and found no difference. PAI-1 gene activation by TNF-α apparently is yet to be defined for the location of the response element and/or the signaling pathway, while TGF-β is the most important cytokine for PAI-1 transcriptional activation through its 5’ proximal promoter.
Keywords: Plasminogen activator inhibitor-1; transforming growth factor-β; tumor necrosis factor-α; MAP kinase; endothelium